Adaptation Under Pressure: Resistance and Stress Response Interplay in Clinical Aspergillus fumigatus Isolates - Ivana Segéňová; Ján Víglaš; Tomáš Pagáč; Petra Olejníková (Journal of Fungi)
Understanding the interplay between antifungal resistance, stress adaptation, and virulence in Aspergillus fumigatus is critical for more effective treatment outcomes. In this study, we investigate six clinical isolates of A. fumigatus from the hospitals of the Czech Republic, focusing on their resistance profiles, stress responses, and survival mechanisms under antifungal pressure. Notably, we have shown that azole-susceptible strains were able to form persister cells under supra-MIC concentrations, highlighting an emerging non-genetic survival mechanism. Stress response profiling demonstrated differential susceptibility to agents targeting signal transduction pathways, as principal component analysis proved that even azole-resistant strains might rely on these pathways. Combinatorial treatment with posaconazole and dithiothreitol enhanced antifungal efficacy regardless of the susceptibility of the strains. Fitness assays revealed that azole resistance imposed a competitive disadvantage in azole-free conditions. In vivo virulence assessment in Galleria mellonella larvae revealed strain-specific pathogenicity that did not directly correlate with resistance. Together, our findings illustrate the multifactorial nature of fungal survival and emphasize that stress adaptation, tolerance, and persistence significantly affect treatment efficacy and outcomes, even in the absence of classical resistance mechanisms. Targeting stress response pathways emerges as a promising strategy to enhance the efficacy of existing antifungal agents and manage resistance in A. fumigatus.